The potential of sonocrystallization in crystal habit modification for improving micromeritic and physicochemical properties of Dapagliflozin - Singh M.; Dhondale M.R.; Agrawal A.K.; Panda S.; Kumar D. (My University, 2025)
Dapagliflozin propanediol monohydrate (DAPA), an antidiabetic drug owing to its needle-shaped crystals exhibits poor micromeritic and physicochemical properties. Crystal habit modification by conventional and sonocrystallization approaches was employed to improve its manufacturability. SEM analysis of sonocrystallized DAPA in acetonitrile (DAPA_SNC3) revealed a rod habit with lower aspect ratio (3.56±0.91) and narrow size distribution (span value-1.37). In case of DAPA_EH and DAPA_CS (solvent evaporation in ethanol:n-hexane, and chloroform, respectively), rod and plate-shaped crystals were obtained with aspect ratios 6.98±5.84 and 6.03±4.21, respectively. All three samples showed significantly improved powder flowability (p<0.0001) compared to DAPA. Further solid-state characterization by FTIR, TGA, DSC, and PXRD showed no polymorphic changes in recrystallized samples. The contact angle studies in water revealed wetting tendency in the following order: SONO_SNC3>SONO_EH>SONO_CS>DAPA. Polar energies of DAPA_SNC3 and DAPA_CS were significantly higher (p<0.01 & p<0.001, respectively) when compared with DAPA. The XPS studies showed increased hydrophilic elements on the surfaces of DAPA_SNC3 crystals which resulted in improved wettability. DAPA_SNC3 among all samples showed highest tensile strength at 200 MPa compression force because of its shape. DAPA_EH showed no significant improvement in IDR profile, while DAPA_CS and DAPA_SNC3 showed significantly faster IDR because of prominent polar functionality (p<0.05 and p<0.0001, respectively). © 2024 Institution of Chemical Engineers